Building Typology of Kadato Kie from Tidore Sultanate - Suci Elvira; Aristotulus Ernst Tungka; Cynthia Erlita Virgin Wuisang (Universitas Khairun, 2021)
The arrival of foreign nations to the Indonesian archipelago, particularly Tidore Island, which is known for its Islamic empire, has impacted the social, cultural, and architectural developments in Tidore. Thus, acculturation of culture and architecture happened where the traditional ones had been assimilated with local culture, including some Arab and Chinese and colonial cultures. Some of these historical heritage buildings are still standing today, especially the Kedaton of the Tidore Sultanate. This study aimed to identify the building typology of the Kedaton (Kadato Kie) of the Tidore Sultanate and elaborate the influence of local and colonial architecture on architectural elements of the Kedaton (Kadato Kie) building of the Tidore Sultanate. This study used a qualitative method with a descriptive approach to reveal the findings through three stages: identification, analysis, and verification. This study focused on the Kedaton of the Tidore Sultanate or Kadato Kie or Kedaton Gunung, the Tidore Sultanate's palace. The Kedaton is located in Soasio Sub-district Tidore Kepulauan City, North Maluku Province, after undergoing reconstruction. Therefore, this is expected to provide theoretical and practical advantages in architecture by analyzing the type and characteristics of the building.